Media Power and the Construction of Reality: A Critical Discourse Analysis Using Teun A. Van Dijk's Model on the News of the Exploding Pager on Al Jazeera Net: Quwwat al-Wasā'il wa Bunyat al-Realīyah: Tahlīl al-Khiṭāb al-Nuqadī bi-Istikhdām Nīzām Teun A. Van Dijk fī Akhbār Infijār al-Muqabbir fī Al-Jazeera Net - Nur Hasaniyah; Siti Zubaidah (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2025)
This research analyzes the news report entitled “ما جهاز البيجر الذي انفجر في عناصر حزب الله؟” published by Al Jazeera Net, using the Critical Discourse Analysis (AWK) approach of Teun A. van Dijk model. The purpose of this research is to reveal how the media frames reality, shapes public opinion, and represents ideology and power relations in the context of the Israeli-Palestinian conflict. This research uses a descriptive qualitative approach with a critical discourse analysis method that includes three main dimensions: macrostructure (theme), superstructure (text scheme), and microstructure (lexical, syntactic, and rhetorical aspects). The results show that Al Jazeera actively shapes social reality through language and representation strategies, by framing Hezbollah as the victim and Israel as the actor suspected of carrying out the cyberattack. The use of technical narratives, quotation of international sources, and the selection of diction that builds a conspiratorial impression shows the media's role as an ideological agent. In this context, Al Jazeera not only conveys information, but also reproduces meanings that favor certain groups. This study confirms that the media has a dimension of power in shaping the construction of social reality through discursive practices. يتناول هذا البحث بالتحليل التقرير الإخباري المعنون